Performance evaluation in the UEFA Champions League - Zambom-Ferraresi, F.; Garcia-Cebrian, L. I.; Lera-Lopez, F.; Iraizoz, B. (Journal of Sports Economics, 2017)
This article aims to evaluate the sports performance of teams that have participated in the Union of European Football Associations (UEFA) Champions League (UCL) during the last 10 seasons (2004-2005 to 2013-2014). Technical efficiency is estimated using well-known data envelopment analysis (DEA) approaches and a bootstrapped DEA model. To solve the problem of measuring sporting results as output in knockout competitions, we propose the use of the coefficients applied by the UEFA from UCL revenue distribution. The results obtained show first that there is a high level of inefficiency in UCL over the period studied: Only 10% of the teams seem to be efficient. Also, the teams have many problems in maintaining their efficiency during the seasons. Second, the champion is always efficient. Third, we identify two sources of inefficiency: waste of sports resources and the selection of sporting tactics. Finally, from a methodological perspective, the output measure proposed seems to be suitable to represent reliably the sports results achieved by clubs in this qualifying competition type. Furthermore, our results are robust when applying alternative estimation methods. Regarding the results, some management implications are discussed and suggestions are made to boost the efficiency in inefficient clubs.